PELAKSANAAN PEMBERIAN IZIN TOKO SWALAYAN STUDI KASUS DAILLY MART DAN PASAR SAIL DI KECAMATAN SAIL KOTA PEKANBARU TAHUN 2020 - Intan Dewi Lestari; Sofyan Hadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Pekanbaru City Government Policy Number 09 of 2014 concerning Management of People's Markets, Shopping Centers and Supermarkets. Where this policy regulates the implementation of licensing for the establishment of supermarkets. The problem in this study is that it is not in accordance with the rules contained in the regional regulation with the facts on the ground which backfire for the aggrieved party. The purpose of this study is to determine the implementation of supermarket offerings and want to know how the impact of the existence of supermarkets on traditional markets. The research methodology uses a qualitative research approach with descriptive type. This method aims to get a picture that really explains the Pekanbaru City Policy on the Granting of Government Business Permits in an Effort to Protect the Existence of Traditional Markets in Sail District. The results of this study are the implementation of the policy of Regional Regulation No. 9 of 2014 concerning the Management of People's Markets, Shopping Centers and Supermarkets in the Pekanbaru City area in this case is still not running optimally, one of which is about the distance between supermarkets and traditional markets in Sail subdistrict. , where right in front of the sail market stands a supermarket (Daily Mart) which is considered to have violated the rules contained in Perda No. 09 of 2014. Where in this study there are several aspects that affect the implementation of public policy, namely, bureaucratic structure, communication, disposition or attitude of implementers and resources. The impact of the existence of Daily Mart on the sail market is that it has an impact on the socio-economic community Keywords: Implementation, Policy, Daily mart